Perspektif Hukum Islam terhadap Tanggungjawab (Hadhanah) kepada Anak ketika Orang Tua Bercerai - Faiz Zainuddin; Ali Burhan (Al-Adillah: Jurnal Hukum Islam, 2023)
There are many things that a husband and wife should ask when deciding to divorce. Apart from arbitrary assets, another thing that must be considered is the distribution of child custody in a divorce. by both parents may not harm the fulfillment of children's rights which are also regulated by the state through the child custody law through Law Number 23 of 2002 concerning Child Protection. In the General Provisions Article 1 point 11 it is explained that parenting is the power of parents to raise, educate, nurture, care for, protect and develop children according to religion and their abilities, talents and interests. According to Article 41 of Law Number 1 of 1974 concerning Marriage, a husband and wife are still obliged to look after and educate their children for the benefit of the child itself. Divorce also does not eliminate the father's obligation to be responsible for all the upbringing and education that children need. However, the court may decide that the mother also demands it under certain conditions. The court also has the right to determine which child custody rights should be given to the mother or father, especially if there are household rights.